Analisis Faktor-faktor Perubahan Design Terhadap Proyek Konstruksi Pelebaran Jalan Tol Jakarta-Merak (Area Cikupa) - Yunita Dian Suwandari; Oties T. Tsarwan (Engineering, MAthematics and Computer Science (EMACS) Journal, 2020)
In every project, job changes are always happening and almost unavoidable. One of the factors that influence job change is a design change. This study analyzes the design changes that have caused delays in the Jakarta-Merak toll road widening project in the Cikupa area—collecting data using literature studies and questionnaires with five Linkert scales. The analysis used SPSS version 22. The research finding is five variables of design changes and changes due to the land’s location to be used as a project, which are the leading causes of changes in this project’s design.